A quasi-experimental examination of weight-reducing dehydration practices in collegiate male rowers - Kelly, D. J.; West, S. L.; O`Keeffe, N.; Brown, L. E. (BMC Sports Science, Medicine and Rehabilitation, 2021)
Background Lightweight rowers commonly utilize weight loss techniques over 24-h before competition to achieve the qualifying weight for racing. The objective was to investigate, using a quasi-experimental design, whether changes in weight resulting from dehydration practices are related to changes in proxies of bodily systems involved in rowing and whether these relationships depend on the dehydration technique used.